Erloschene Liebe? Das Auto in der Verkehrswende: Soziologische Deutungen - Ruhrort, Lisa; Scherf, Christian; Knie, Andreas; Canzler, Weert (transcript, 2018)
The privately owned car was an object of desire and a symbol of a happy life. It was collectively loved by the middle class and those who strove towards that social level. Yet this emotional affection has been dwindling particularly in cities. At least there it has become obvious that the limits of fossile automobilism have been reached. There are simply too many cars around. Now the transformation of traffic is on the agenda. Only traffic systems that will be able to still individualize when resources become rare are sustainable. Using cars instead of owning them will become attractive in connection with digital platforms; bicycles are becoming more popular, especially in cities. Mobility services are coming out of the wings and can be used flexibly yet routinely thanks to real time information. Privately owned vehicles, however, are still privileged by the current legal framework. Yet the preferences of the mainly urban population and the available digital options are pointing in another direction: The progressing individualization will find other means than privately owned cars.